EFEKTIVITAS DAN PROBLEMATIKA MATERI BIMWIN (STUDI KASUS KANTOR URUSAN AGAMA KECAMATAN TAMANSARI KABUPATEN BOGOR) - Adien Maya Azzahra; Kayla Tabita Salsabila; Nezla Shabira Wijaya; Khairunnisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Marriage Guidance (Bimbingan Perkawinan or BIMWIN) is a preventive program initiated by the Indonesian Ministry of Religious Affairs to equip prospective couples with the knowledge and skills needed to build a harmonious (sakinah) family. This study aims to analyze the effectiveness and challenges of BIMWIN materials at the Office of Religious Affairs (KUA) of Tamansari District, Bogor Regency. The research employed a qualitative case study approach using in-depth interviews, observations, and document analysis. The findings indicate that the BIMWIN materials are based on the Fondasi Keluarga Sakinah handbook and are delivered by certified facilitators. However, the effectiveness of the program is constrained by limited time, facilities, funding, and participant engagement. In addition, the materials have not fully addressed contemporary issues, such as premarital mental readiness, family digital literacy, cyber infidelity, digital parenting, and dual-career families. Therefore, BIMWIN requires continuous improvement through the enrichment of its materials, the adoption of more participatory learning methods, and stronger institutional support to enhance its role in strengthening family resilience.